APLIKASI KONSORSIUM PUPUK HAYATI TERHADAP POPULASI BAKTERI PELARUT FOSFAT DAN BOBOT KERING PADI (Oryza sativa L.) PADA BEBERAPA TINGKAT SALINITAS - Puspafirdausi, Fidya A.; Sofyan, Emma Trinurani; Fitriatin, Betty Natalie (Jurnal Agroekoteknologi, 2017)
Salinization of soil in coastal area is a serious problem and is increasing steadly. Application biofertilizer consortium is able to improve productivity of rice crops (Oryza sativa L.) grown in saline soils. Biofertilizer supplies nutrients and phytohormones that are beneficial for plant. The aim of this research was to find combination effects of biofertilizer consortium on population of phosphate solubilizing bacteria and dry weight of paddy grown in several level of salinity. This research was conducted from December 2016 to February 2017 at greenhouse of Faculty of Agriculture, Universitas Padjadjaran with altitude 752 meters above sea levels. This research used randomized block design single factor experiment which consist of eight combinations of biofertilizer (Azotobacter sp., Azospirillum sp., endophytic bacteria, PSB, and AMF) and salinity with four replications: A (non saline 0 mmhos cm-1), B (non saline of 0 mmhos cm-1 + biofertilizer), C (salinity of 2 mmhos cm-1), D (salinity of 2 mmhos cm-1+ biofertilizer), E (salinity of 4 mmhos cm-1), F (salinity of 4 mmhos cm-1+ biofertilizer), G (salinity of 6 mmhos cm-1), H (salinity of 6 mmhos cm-1+ biofertilizer). The result showed that at salinity level of 2-4 mmhos cm-1 the crops still survived growing under salinity stress. Salinity treatment of 2 mmhos cm-1 + biofertilizer significantly affected popuation of phosphate solubilizing bacteria and salinity treatment of 4 mmhos cm-1 + biofertilizer significantly affected dry weight of rice.